Recent anomalous deformation of the ground surface in fault zones: shear or tensile faulting? - Yu. O. Kuzmin (Геодинамика и тектонофизика, 2018)
Various definitions of the kinematic types of faults are reviewed. The degree of symmetry in the distribution of anomalous displacements of the ground surface is proposed as a morphological criterion for identifying the types of faults based on geodetic observations. Local anomalies of vertical displacements identified by geodetic observations in the fault zones are analysed by types. It is revealed that 88 % of the analysed anomalies show local symmetrical subsidence of the ground surface near the faults. Morphologically, these anomalies correspond to the subvertical tensile faults. Mechanisms of three types (block, dislocation, and parametric) are discussed considering the formation of the observed displacements in the zones of activation of the tensile faults. A comparison of the calculated and observed displacements of the ground surface shows that the best consistency between the theory and the observations is achieved using the model of local parametric excitation of deformation under quasi-static regional loads and the theory of strain nuclei (soft inclusions).